Corporate Crime Prevention Through Sustainable Governance and Regulatory Reform - Ali Kusumo, Bambang; Rustambekov Islambek Rustambekovich; Yakubov Axtam Nusratilloyevich; Xodjayev Baxshillo Kamolovich (Lembaga Contrarius Indonesia, 2025)
Corporate crime significantly undermines economic integrity, disrupts environmental sustainability, and erodes public trust in governance institutions. In the Indonesian context, the complexity of corporate liability and the limited effectiveness of law enforcement have constrained efforts to prevent corporate offenses. This study critically examines how sustainable governance and regulatory reform contribute to strengthening mechanisms for corporate crime prevention. The research employs a normative juridical method and systematically analyzes secondary data consisting of primary, secondary, and tertiary legal materials through a qualitative descriptive approach. The analysis demonstrates that first, the application of sustainable governance principles such as transparency, accountability, and ethical compliance functions as an effective preventive framework against corporate misconduct. Second, the current legal structure provides a sufficient normative foundation for corporate accountability; however, law enforcement remains inconsistent due to institutional fragmentation and inadequate coordination among agencies. Third, the integration of sustainability indicators and corporate responsibility standards into legal enforcement frameworks becomes a necessary reform priority. The study concludes that the combination of sustainable governance and regulatory reform reinforces corporate integrity, promotes a culture of compliance, and strengthens legal certainty to ensure long term effectiveness in combating corporate crime.